Modeling Hydrologic Response to Land Use and Climate Change in the Krueng Jreu Sub Watershed of Aceh Besar - Teuku Ferijal; Mustafril Bachtiar; Dewi Sri Jayanti; Dahlan Jafaruddin (Aceh International Journal of Science and Technology)
Soil and Water Assessment Tool (SWAT) model was used to simulate impact of landuse and climate change on water resources in Krueng Jreu subwatershed located in Aceh Province – Indonesia. The subwatershed is a primary source of water to irrigated 233.52 km2 paddy field area through a surface irrigation system. The model performance was considerably good in predicting streamflow. The coefficients of determination varied between 0.58 and 0.72, while the Nash-Sutcliffe coefficients (ENS) ranged between 0.65-0.72 and the percentage bias were in the range of -0.36 to 2.30. Scenarios were applied to the best fit model to evaluate watershed responses to land use and climate changes. The model predicted increases in both runoff and water yield by 1% and 0.1% respectively as the result of increasing 15% settlement area. When all agricultural land within subwatershed converted to forest, water yield would increase by 1% during dry period and runoff contribution would decrease by 5%. Increases in surface flow by 23.6% and water yield by 15.1% were found under scenario of increasing 10% of daily precipitation. Increasing in evapotranspiration caused by an increase of 1.5⁰C in daily air temperature would decrease surface flow and water yield by 0.8% and 1.3%, respectively. Combination scenarios of changes in daily temperature and precipitation would increase evapotranspiration rate, annual water yield and runoff contribution.